What is the role of volunteer work in protected areas? A case study in Brazil - Silveira Junior, Wanderley Jorge; Santana, Lucas Dezidério; Souza, Cléber Rodrigo; Yaguinuma, Renata Vichi; Gomes, Carolina Ribeiro; Fontes , Marco Aurélio Leite (Sociedade & Natureza, 2022)
Currently, protected areas around the world have a demand for volunteer work. At the same time, people in several countries that house protected areas seek out these spaces to serve as volunteers. This process occurs in a scenario strongly influenced by the neoliberal economy, which is marked by cuts in environmental management budgets and increased protected areas visitation. Based on this context, the objective was to analyze the role of volunteer work in protected areas in the context of neoliberal paradigm predominance. For this purpose, it was established a current overview of volunteer activity through a case study in Brazil by collecting information from volunteers and managers, heads or managers of protected areas receptive to volunteer work in interviews using structured questionnaires. It was found that Parques Nacionais are the categories with the greatest demand for volunteer work. It was also found the most part of volunteers is between 20 and 30 years old, and their education level is higher education in undergraduate courses related to biological sciences. It was identified significant differences between the perceptions of managers and volunteers about volunteer work objectives. However, both groups indicated that “Environmental education/environmental interaction and interpretation” and “Support for visitation” are the most frequently performed activities, and the main form of support and trade-off for volunteer work is the offering of certificates. Thus, volunteer work seeks to contribute to the protected areas objectives by supporting the management of these areas during public use activities. However, in the current scenario, this work is palliative in the face of the impacts of the dismantling of environmental policy that affects most countries that have Protected areas and have surrendered to neoliberal conservation.